2017
DOI: 10.1002/jat.3514
|View full text |Cite
|
Sign up to set email alerts
|

Butyltin compounds alter secretion of interleukin 6 from human immune cells

Abstract: Butyltins (BTs), tributyltin (TBT) and dibutyltin (DBT) are organotin compounds that have been used in a variety of industrial applications; as a result, these compounds have been found in human blood. Interleukin (IL)-6 is a proinflammatory mediator that is produced by T lymphocytes and monocytes. It is responsible for immune response regulation as well as tissue repair and cellular growth. Both BTs decrease the ability of human natural killer cells to destroy tumor cells and alter the secretion of proinflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 73 publications
(145 reference statements)
1
7
0
1
Order By: Relevance
“…Thus, TBT is an inducer of oxidative stress and plays an important role in the positive modulation of pro-inflammatory cytokines ( 45 ). This is consistent with data showing a decreased activity of SOD, CAT, and GPX in other species ( 46 , 47 ), a higher expression of HSP70 in common carp ( 48 ), an increased IL-1β secretion by human immune cells ( 49 ), an increased IL-6 production in human peripheral blood mononuclear cells ( 50 ), and higher TNF-α levels in mouse serum ( 51 ).…”
Section: Introductionsupporting
confidence: 91%
“…Thus, TBT is an inducer of oxidative stress and plays an important role in the positive modulation of pro-inflammatory cytokines ( 45 ). This is consistent with data showing a decreased activity of SOD, CAT, and GPX in other species ( 46 , 47 ), a higher expression of HSP70 in common carp ( 48 ), an increased IL-1β secretion by human immune cells ( 49 ), an increased IL-6 production in human peripheral blood mononuclear cells ( 50 ), and higher TNF-α levels in mouse serum ( 51 ).…”
Section: Introductionsupporting
confidence: 91%
“…These include interferon gamma (IFNγ), tumor necrosis factor alpha (TNFα), IL-1β, and IL-6 (Hurt et al . 2013; Lawrence et al, 2015; Brown and Whalen, 2015; Brown et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…TBT has been shown to alter the secretion of both IL-1β and IL-6 from human lymphocytes (Brown and Whalen, 2015; Brown et al, 2018). The current study examines whether these alterations in secretion are due to changes in the lymphocytes’ synthesis of these cytokines or if it is simply due to changes in the secretion of pre-existing cytokine.…”
Section: Introductionmentioning
confidence: 99%
“…This OTs’ presence in human blood was able to compromise the natural killer (NK) cells activity in vitro ( 9 ). Also, Brown and colleague, in 2017 ( 10 ), reported that OTs alters the interleukin 6 (IL-6) secretion from human immune cells and consequently, affect the immune competence ( 10 ). In 2014, Valenzuela and colleagues ( 11 ) developed an efficient methodology capable to identify 11 OT compounds in urine from harbor workers exposed to antifouling paints.…”
Section: Introductionmentioning
confidence: 99%